Bilateral Simultaneous Cochlear Implantation in Children: Report of a Case and Review of Literature - Varghese, Ajoy Mathew (Springer-Verlag, 2011)
The benefits of bilateral cochlear implant in adults are well established. Auditory ability in children is also substantially improved by binaural hearing. We report the first case of bilateral simultaneous paediatric cochlear implant in India and discuss the merits of bilateral implant.